Characterization of mitochondrial proteomes of nonbilaterian animals. Issue 12 (12th November 2018) - Muthye, Viraj; Lavrov, Dennis V.
Summary: Mitochondria require ~1, 500 proteins for their maintenance and proper functionality, which constitute the mitochondrial proteome (mt‐proteome). Although a few of these proteins, mostly subunits of the electron transport chain complexes, are encoded in mitochondrial DNA (mtDNA), the vast majority are encoded in the nuclear genome and imported to the organelle. Previous studies have shown a continuous and complex evolution of mt‐proteome among eukaryotes. However, there was less attention paid to mt‐proteome evolution within Metazoa, presumably because animal mtDNA and, by extension, animal mitochondria are often considered to be uniform. In this analysis, two bioinformatic approaches (Orthologue‐detection and Mitochondrial Targeting Sequence prediction) were used to identify mt‐proteins in 23 species from four nonbilaterian phyla: Cnidaria, Ctenophora, Placozoa, and Porifera, as well as two choanoflagellates, the closest animal relatives. Our results revealed a large variation in mt‐proteome in nonbilaterian animals in size and composition. Myxozoans, highly reduced cnidarian parasites, possessed the smallest inferred mitochondrial proteomes, while calcareous sponges possessed the largest. About 513 mitochondrial orthologous groups were present in all nonbilaterian phyla and human. Interestingly, 42 human mitochondrial proteins were not identified in any nonbilaterian species studied and represent putative innovations along the bilaterian branch. Several of these proteins were involved in apoptosis and innate immunity, two processes known to evolve within Metazoa. Conversely, several proteins identified as mitochondrial in nonbilaterian phyla and animal outgroups were absent in human, representing cases of possible loss. Finally, a few human cytosolic proteins, such as histones and cytosolic ribosomal proteins, were predicted to be targeted to mitochondria in nonbilaterian animals. Overall, our analysis provides the first step in characterization of mt‐proteomes in nonbilaterian animals and understanding evolution of animal mt‐proteome. © 2018 IUBMB Life, 70(12):1289–1301, 2018